Hypoxia-inducible factor-1alpha activation in HPV-positive head and neck squamous cell carcinoma cell lines - Knuth, Jennifer; Sharma, Shachi J.; Würdemann, Nora; Holler, Claudia; Garvalov, Boyan K.; Acker, Till; Wittekindt, Claus; Wagner, Steffen; Klussmann, Jens P.; Justus Liebig University Giessen (My University, 2017)
Purpose: Human papillomavirus (HPV) is a causative agent for a rising number of head and neck squamous cell carcinomas (HNSCC), which are characterized by distinct tumor biology. Hypoxia inducible-factor (HIF) signaling influences initiation and progression of carcinogenesis and HPV oncoproteins have evolved to highjack cellular pathways for viral reproduction. Therefore, we investigated whether HPV activates HIF-1alpha expression in HNSCC.Experimental Technique: HPV-positive and -negative HNSCC cells were examined for adaptive responses to hypoxia. Expression of HIF-1alpha, prolyl hydroxylasedomain protein 2 (PHD2) and E-cadherin was analyzed by Western blotting, immunofluorescence (IF) microscopy and migration/wound healing assays.Results: HPV-positive HNSCC cells showed higher HIF-1alpha and PHD2 protein levels under normoxia and hypoxia. HIF-1alpha hydroxylation was reduced in HPV-positive HNSCC cell lines under PHD and proteasomal inhibition. In vitro wound healing assays showed impairment of migration and proliferation by HIF-1alpha pathway activation in HPV-negative cell lines only. In contrast, migration and proliferation in HPV-positive cell lines was impaired by HIF-1alpha specific siRNA.Conclusions: HPV-positive HNSCC cells show activation of the HIF pathway and adaptation to HIF-1alpha upregulation, representing potential therapeutic targets in this emerging tumor entity.
Keywords: human papillomavirus (hpv); head and neck squamous cell carcinoma (hnscc); hypoxia; hypoxia inducible factor-1alpa (hif-1alpha); ddc:610